A 3D Progressive Failure Model for predicting pseudo-ductility in hybrid unidirectional composite materials under fibre tensile loading. (April 2018) - Guerrero, J.M.; Mayugo, J.A.; Costa, J.; Turon, A.
Abstract: This paper presents a three-dimensional Progressive Failure Model based on the chain of bundles able to represent the stiffness loss in unidirectional composite materials loaded in the fibre direction. A representative volume element with a random distribution of fibres with their own radius is considered. Complete stress distributions around fibre breaks are obtained by associating a damage variable to the loss of stress transfer capability along the ineffective length and applying local stress concentrations. The model has been validated by comparing it against the literature results and exhibits good agreement with hybrids and non-hybrid composites. The aim of this model is to simulate the tensile response of unidirectional composite systems dominated by fibre fragmentation mechanisms using a very reduced computational effort, even for larger representative volume elements, compared to micro-mechanical finite element models.